Combination of voxel based morphometry and diffusion tensor imaging in patients with Alzheimer's disease - Ibrahim, Ibrahim; Horáček, Jiří; Bartoš, Aleš; Hájek, Milan; Řípová, Daniela; Brunovský, Martin; Tintěra, Jaroslav (Neuro-endocrinology letters, 2009)
OBJECTIVE: The aim of the study was to assess structural changes in gray matter (GM) volume and fractional anisotropy (FA) in patients with Alzheimer's disease (AD) compared to control subjects using Voxel-Based Morphometry (VBM). Fractional anisotropy in the corpus callosum of both groups was also calculated using ROI analysis. METHODS: Twenty-one patients and twenty-three control subjects underwent MRI examination using T1-weighted 3D MPRAGE sequence and diffusion spin-echo echo-planar imaging sequence in six directions. Structural MRI analyses for GM volume and FA were performed using an optimized VBM protocol implemented in SPM5. The influence of age and Mini-Mental State Examination (MMSE) was dealt with multiple regression analysis either for the whole group or for AD patients and controls separately. RESULTS: Patients showed significant reduction of GM volume mainly in the temporal lobes. In AD patients, no correlation was observed between GM volume and age or MMSE. FA was reduced in AD patients mainly in frontal and temporal lobes. In both groups no correlation was found between FA and age or MMSE. Patients with AD showed a significant decrease in FA and an increase in mean diffusivity (p<0.0001) in the corpus callosum. CONCLUSIONS: In patients with AD we observed a significant reduction in FA values and GM volume; however, no correlation with age and MMSE was proven for both FA and GM for AD patients. This finding supports the hypothesis that morphological changes in patients with AD are not a continuous aging related process but represent qualitative changes.
Keywords: velikost orgánu; Anisotropy; Male; Echo-Planar Imaging; Organ Size; corpus callosum; difuzní magnetická rezonance; Alzheimerova nemoc; Age Factors; Alzheimer Disease; Aged; mužské pohlaví; senioři; psychologické testy; senioři nad 80 let; lidé; ženské pohlaví; Diffusion Magnetic Resonance Imaging; Humans; anizotropie; Corpus Callosum; věkové faktory; Aged, 80 and over; Psychological Tests; Female; echoplanární zobrazování; lidé středního věku; Middle Aged